2015
DOI: 10.1089/ten.tea.2014.0008
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Forces Applied on a Cell-Embedded Three-Dimensional Scaffold Can Direct Early Differentiation of Embryonic Stem Cells Toward the Mesoderm Germ Layer

Abstract: Mechanical forces play an important role in the initial stages of embryo development; yet, the influence of forces, particularly of tensile forces, on embryonic stem cell differentiation is still unknown. The effects of tensile forces on mouse embryonic stem cell (mESC) differentiation within a three-dimensional (3D) environment were examined using an advanced bioreactor system. Uniaxial static or dynamic stretch was applied on cell-embedded collagen constructs. Six-day-long cyclic stretching of the seeded con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Besides stiffness and geometry, mechanical forces also play an important role in the directed differentiation of stem cells, and the direction, magnitude, and duration of shear stress have been shown to guide the differentiation of ESCs . Dado‐Rosenfeld et al showed that early differentiation of ESCs was influenced by tensile forces on 3D collagen constructs, and 6 d cycles of stretching and relaxing of the seeded constructs led to a fourfold increase in Brachyury (BRACH‐T) expression, which is a marker of the primitive streak phase of gastrulation …”
Section: Stem Cell Biology In 3d Culturementioning
confidence: 99%
“…Besides stiffness and geometry, mechanical forces also play an important role in the directed differentiation of stem cells, and the direction, magnitude, and duration of shear stress have been shown to guide the differentiation of ESCs . Dado‐Rosenfeld et al showed that early differentiation of ESCs was influenced by tensile forces on 3D collagen constructs, and 6 d cycles of stretching and relaxing of the seeded constructs led to a fourfold increase in Brachyury (BRACH‐T) expression, which is a marker of the primitive streak phase of gastrulation …”
Section: Stem Cell Biology In 3d Culturementioning
confidence: 99%
“…In 3D culture systems, a different stiffness threshold of the materials was also found to promote the differentiation of human ESCs into each germ layer, suggesting that the mechanical stimuli necessary for directing cell fate can be recapitulated into 3D biomaterials . Analogously, using an advanced bioreactor system, the impact of tensile forces on cell differentiation within a 3D collagen construct was demonstrated when uniaxial static or dynamic stretch was utilized on mouse ESC‐embedded matrices . When Schwann cells were encapsulated within alginate‐based hydrogels using varying alginate concentrations, the mechanical properties of the materials exerted an important effect on the performance of these cells .…”
Section: Engineering a 3d Home For Cell Accommodationmentioning
confidence: 99%
“…Recent works have attempted to optimize blood vessel network properties, such as geometry, maturity, and stability, by supplementing cultures with biological factors (8), biomaterials (9), and geometrical constraints (10,11). Although mechanical forces play a central role in all biological processes and have been demonstrated to influence cell differentiation (12), shape (13), migration (14) and organization (15), they have yet to be comprehensively investigated in relation to vascular network assembly. These forces can include both external forces, in the form of shear stress or tensile and compression forces (16), as well as cell-induced contractile forces (17).…”
mentioning
confidence: 99%